Prevalence and genotyping of Giardia duodenalis among Arabian horses in Ahvaz, southwest of Iran - H. Jafari (Archives of Razi Institute, 2016)
Giardia duodenalis is globally recognized as an important zoonotic intestinal protozoan parasite. So far, eight assemblages of G. duodenalis (A-H) have been identified. Substantial evidence suggests the zoonotic potential of assemblages A, B, and E in livestock. In this study, the genotype of Giardia duodenalis isolates was genetically identified by determining the sequence of ssu-rRNA gene and performing polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) on glutamate dehydrogenase gene of the parasite in Arabian horses from Ahvaz, located in southwest of Iran. The results revealed that assemblages AI and E (livestock-associated G. duodenalis) were present in horse isolates. Also, based on the findings, prevalence of G. duodenalis infection among horses was estimated at 35.7%. The results indicated that G. duodenalis is highly prevalent among Arabian horses, posing a zoonotic risk for giardiasis in Ahvaz, Iran.